2018
DOI: 10.17759/exppsy.2018110305
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transfer of implicit knowledge of artificial grammar under sensorimotor activity

Abstract: The article is addressed on research aimed to discover effect of transfer of implicit knowledge of artificial grammar on sensorimotor tasks solving. Meaning of implicit knowledge in actual cognitive activity has been considered. 40 volunteers took part in experiment, ages 18 to 43 years. Participants of experiment implicit learned the rule of artificial grammar. The task of control phase was to solve the sensorimotor task — to react by pressing of certain key under appearance of green or yellow circle. In expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…It was found that the subjects of the experimental group performed sensorimotor tasks significantly faster, but at the same time they did not realize a pattern of stimulus presentation. Presumably, the subjects of this group implicitly established a connection between the line and the color of the circle, which allowed them to expect the appearance of a green circle after a grammatical line and respond faster (Kryukova, Agafonov, Burmistrov, Kozlov, & Shilov, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the subjects of the experimental group performed sensorimotor tasks significantly faster, but at the same time they did not realize a pattern of stimulus presentation. Presumably, the subjects of this group implicitly established a connection between the line and the color of the circle, which allowed them to expect the appearance of a green circle after a grammatical line and respond faster (Kryukova, Agafonov, Burmistrov, Kozlov, & Shilov, 2018).…”
Section: Introductionmentioning
confidence: 99%